K-9 Police Dog Bite - Vy Han; John R. Marshall (eScholarship Publishing, University of California, 2017)
History of present illness: A 30-year-old male who was brought into the emergency department (ED) by police officers after being bitten in the right lower extremity by a police German Shepard after attempting to flee authorities on foot. The patient stated that the dog immediately bit down on his right calf and proceeded to violently shake its head side to side without releasing its grip until police manually pulled the dog off of him. Upon arrival to the ED, he was tachycardic in the 120's, complaining of severe, throbbing, sharp pain in the right lower extremity, and was neurovascular intact on exam. Significant findings: The photograph is of the anterior compartment of the right lower leg demonstrating multiple deep lacerations with exposed and torn muscle. X-ray showed no foreign body. Discussion: Police dog bites should be treated more cautiously than typical dog bites because these highly-trained dogs are generally larger breeds which are taught to subdue suspects with a bite-and-hold technique rather than bite and release. This can lead to extensive crush injuries, fractures, large caliber lacerations with associated muscle tissue injury and/or severe neurovascular compromise.1 Hence, police dog bites often require provocative diagnostic testing, specialist consultation for possible operative repair, and aggressive irrigation and ultimately admission for intravenous antibiotics.1 This patient's wound was aggressively irrigated and evaluated by plastic surgery in the ED. He was ultimately admitted for intravenous antibiotics, pain control, wound care, and healing by secondary intention.